Environmental pollution and protection - Chand, Attar (New Delhi : Deep & Deep Publications, 1989)
Contributed research papers.
Includes bibliographical references and index.
Keywords: Environmental policy; Environmental policy -- India; Pollution -- Environmental aspects; Environmental law -- India